Cholecystectomy and the risk for developing colorectal cancer and distal colorectal adenomas - Schernhammer, E S (Nature Publishing Group, 2003)
Earlier work describes a modest association between cholecystectomy and the risk of colorectal cancer. We conducted a prospective study of 85 184 women, 36–61 years old, who had no history of cancer to evaluate whether known risk factors for colorectal cancer, including dietary history, that have not been controlled for in previous analyses can help explain the observed association. During 16 years of follow-up, 877 cases of colorectal cancer were documented and 1452 women who underwent endoscopy during the follow-up time were diagnosed with distal adenomas. After adjustment for age and other known or suspected risk factors, we found a significant, positive association between cholecystectomy and the risk of colorectal cancer (multivariate relative risk RR 1.21, 95% CI 1.01–1.46). The risk was highest for cancers of the proximal colon (RR 1.34, 95% CI 0.97–1.88) and the rectum (RR 1.58, 95% CI 1.05–2.36). However, we did not observe a significant association between cholecystectomy and distal colorectal adenomas. In this large prospective cohort study, a history of cholecystectomy appears to increase modestly the risk of colorectal cancer, even after adjustment for other colorectal cancer risk factors.